Green Accounting and Its Implementation to Firm Value in Mining Companies of Indonesia - Martini, Martini; Marakesuma, Indrawati; Triharyati, Eri; Nurhayati, Yuli; Andrialdo, Arisky; Yavanda, Sendi; Facriyah Pratama Muri, Febi (ADPEBI, 2022)
Green accounting encourages companies to carry out activities that have a positive impact on the environment so as to have a positive impact on the firm value and the future of the company. This study investigates the effect of green accounting on firm value which is considered to give a positive signal to investors' assessment of investing in the future. The research method uses SmartPLS 3.0 with green accounting variables proxied by the PROPER value and environmental costs and the firm value variable as proxied by ROE and PER. The results of the study prove that green accounting has no effect on firm value with a coefficient of 0.347 and a t statistic of 1.805, it is concluded that H0 is accepted. Green accounting disclosed by mining sector companies is only carried out as a fulfillment of applicable regulations and does not provide a good signal by investors so that it does not increase the value of the company.